PLANKTON DIVERSITY CHANGES WITH SLIGHT VARIATION IN PHYSICO-CHEMICAL PARAMETERS OF SOME LOTIC AND LENTIC WATER BODIES OF BANKURA DISTRICT OF WB, INDIA - MAJUMDER, SURAJIT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Water is the main source of survival for all the living organisms. Still people use it in a very casual way. As a result of unaware use of water, some changes have taken place in physico-chemical parameters followed by plankton diversity of pond and river water of Bankura district, West Bengal, India. The district Bankura has ranked first in pisciculture (particularly in spawn production) within WB (according to the Office of the Additional Director of Fisheries, Bankura). The village Ramsagar of Onda Block of Bankura district is widely known for the fish spawn production in its more than 250 fish hatcheries spread over the village. The district town Bankura is also full of water bodies like ponds, reservoirs, rivers etc.; still no such outcome is there from pisciculture point of view. The present study mainly focused on the changes in plankton diversity due to slight change in physico- chemical parameters of the water. The sampling was done in the three main rivers of Bankura district namely Gandheswari, Sali and Dwarakeswar; and the five ponds and one reservoir (Mukutmanipur dam) of Bankura district, where in most cases the urban and rural residents are using the water bodies, regularly for their household and economical purposes like fish culture. The changes in various physico-chemical parameters including water and air temperature, pH, total hardness, total alkalinity, chloride ion, dissolved oxygen etc. were analyzed by consulting standard methods and their effects on plankton diversity was studied microscopically after collecting them through proper way. The result shows that the plankton diversity was high in the static water bodies, like pond and reservoir than the lotic water, like river. An interesting finding is, ponds with lower level of chloride ion concentration contain very high density of plankton (in S-52 and S-54) and low to moderate level of dissolved oxygen. Another finding is, out of the twelve studied water bodies, only two showed high, three showed moderate (S-56, S-58 and S-60) and the rest showed less plankton production. But, both the high productive and the two moderate productive ponds were unable to reach the mark of fish production. Only one moderate productive pond (S-60) showed commendable result from pisciculture point of view; may be due to using of proper organic manure in a very scientific way.